Overview of the brand journey and opportunities for future studies - Loureiro, S. M. C. (Italian Journal of Marketing, 2023)
With this study, brand managers can have an overview of the major concepts and characteristics of brands over time, while academics receive a mapping of the most analyzed topics and suggestions for future research. Based on the documents published in Scopus and Web of Science databases using the word “brand”, this article aims to provide an overview of the brands and suggest opportunities for future research. Text mining clustering allowed the processing of a large amount of information and organized the first overview of the concepts that have been studied. Thus, first, we examine the existing definitions of a brand. Then, we provide a historical perspective of the topics associated with brand constructs and their associations and present a framework for the psychological characteristics of the branding process. Finally, we present the future trends.